Selectivity and efficiency of late transgene expression by transcriptionally targeted oncolytic adenoviruses are dependent on the transgene insertion strategy - Quirin, Christina; Rohmer, Stanimira; Fernandez Ulibarri, Ines; Behr, Michael; Hesse, Andrea; Engelhardt, Sarah; Erbs, Philippe; Enk, Alexander; Nettelbeck, Dirk M. (Human gene therapy, 2011)
Key challenges facing cancer therapy are the development of tumor-specific drugs and potent multimodal regimens. Oncolytic adenoviruses possess the potential to realize both aims by restricting virus replication to tumors and inserting therapeutic genes into the virus genome, respectively. A major effort in this regard is to express transgenes in a tumor-specific manner without affecting virus replication. Using both luciferase as a sensitive reporter and genetic prodrug activation, we show that promoter control of E1A facilitates highly selective expression of transgenes inserted into the late transcription unit. This, however, required multistep optimization of late transgene expression. Transgene insertion via internal ribosome entry site (IRES), splice acceptor (SA), or viral 2A sequences resulted in replication-dependent expression. Unexpectedly, analyses in appropriate substrates and with matching control viruses revealed that IRES and SA, but not 2A, facilitated indirect transgene targeting via tyrosinase promoter control of E1A. Transgene expression via SA was more selective (up to 1,500-fold) but less effective than via IRES. Notably, we also revealed transgene-dependent interference with splicing. Hence, the prodrug convertase FCU1 (a cytosine deaminase-uracil phosphoribosyltransferase fusion protein) was expressed only after optimizing the sequence surrounding the SA site and mutating a cryptic splice site within the transgene. The resulting tyrosinase promoter-regulated and FCU1-encoding adenovirus combined effective oncolysis with targeted prodrug activation therapy of melanoma. Thus, prodrug activation showed potent bystander killing and increased cytotoxicity of the virus up to 10-fold. We conclude that armed oncolytic viruses can be improved substantially by comparing and optimizing strategies for targeted transgene expression, thereby implementing selective and multimodal cancer therapies.